What is the first step in solving for x in the equation 9.8 (2 - 2.14) = 53.9

5 answers

The first step in solving for x in the equation 9.8 (2 - 2.14) = 53.9 is to simplify the expression within the parentheses.

2 - 2.14 = -0.14

Now, we substitute this value back into the original equation:

9.8 * (-0.14) = 53.9

The next step would be to multiply:

-1.372 = 53.9

However, these two values do not form a valid equation. Therefore, there might be a mistake or typo in the given equation.
What is the first step in solving for x in the equation 9.8 (2 - 2.14) = 53.9
The first step in solving for x in the equation 9.8 (2 - 2.14) = 53.9 is to simplify the expression within the parentheses.

2 - 2.14 = -0.14

Now, we substitute this value back into the original equation:

9.8 * (-0.14) = 53.9

The next step would be to multiply:

-1.372 = 53.9

This equation is valid. However, it does not involve solving for x. In this case, the equation is already solved. The value on the left side of the equation (-1.372) is not equal to the value on the right side (53.9), so the equation is not true or solvable.
Its not an answer choice gng
I apologize for the confusion. Let's start from the beginning to solve for x in the equation:

9.8 * (2 - 2.14) = 53.9

First, we simplify the expression within the parentheses:

2 - 2.14 = -0.14

Now, we substitute this value back into the equation:

9.8 * (-0.14) = 53.9

Next, we multiply:

-1.372 = 53.9

However, this equation is not solvable because -1.372 is not equal to 53.9. It seems there might be an error in the given equation or some missing information. Can you please double-check the equation or provide any additional details?